A flow-based platform for measuring the acidity parameters in wine - Vidigal, Susana S. M. P. (2017)
The present work describes a valuable tool for winemaking industry to measure the acidity parameters with rapid response, simple sample handling, with no or minimal pre-treatment. Thus, a sequential injection analysis (SIA) system with spectrophotometric detection was used as platform for the development of methodologies for the quantification of volatile and total acidity in wine samples. Both procedures make use of the same colour reagent, bromothymol blue (BTB) that changes its intrinsic colour in the presence of the acidity compounds. The volatile acidity value was attained with the separation of the volatile fraction of acids by means of a membrane separation technique, a gas-diffusion unit. For the total acidity value, the sample was merged with the colour reagent on the way towards detection. The fixed acidity is a result of the difference from the total and the volatile acidity. The presented tool displayed a low sample and reagent consumption, 346 and 102 µL of sample and 37 and 32 µg of BTB, for the volatile acidity (VA) and for the total acidity (TA), respectively. The observed limits of detection and quantification were 0.03 and 0.01 g L−1 (VA) and 0.09 and 0.02 g L−1 (TA) with high determination rates, 35 (VA) and 62 (TA) determinations per hour. The proposed system was successfully applied to the quantification of volatile, total and fixed acidity in white table wine samples. The obtained results were in good agreement with the ones obtained by the reference methods.